2012
DOI: 10.1515/revneuro-2011-0072
|View full text |Cite
|
Sign up to set email alerts
|

A historical justification for and retrospective analysis of the systematic application of light therapy in Parkinson’s disease

Abstract: For the past 40 years the primary purpose of therapeutics for Parkinson's disease (PD) has been to replace deficient dopamine (DA) in the nigrostriatal dopamine (NSD) system. Even in the presence of limited efficacy, abundant side effects and impoverished quality of life, the involvement of other systems in the aetiology and treatment of this disorder has been sorely neglected and the excessive use of DA replacement therapy (DART) continues on a global basis. Recent scientific work suggests that the retina pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 106 publications
6
109
0
8
Order By: Relevance
“…The results revealed that BLT facilitated motor performance recovery of PD patients, and decreased the dosage of dopamine replacement drugs. Meanwhile, improvements in mood and sleep quality were also observed in patients with other neurological disorders [110]. These studies have demonstrated the enabling effect of BLT on motor and non-motor manifestations in PD.…”
Section: Circadian Therapymentioning
confidence: 60%
“…The results revealed that BLT facilitated motor performance recovery of PD patients, and decreased the dosage of dopamine replacement drugs. Meanwhile, improvements in mood and sleep quality were also observed in patients with other neurological disorders [110]. These studies have demonstrated the enabling effect of BLT on motor and non-motor manifestations in PD.…”
Section: Circadian Therapymentioning
confidence: 60%
“…Показана ее эффективность в лечении инсом-нии и депрессии [131,132]. Исследования фототера-пии у пациентов с БП немногочисленны и прово-дились на небольших группах больных [133][134][135]. В большинстве исследований применение фототе-рапии сопровождалось уменьшением проявлений инсомнии и депрессии при БП.…”
Section: лечение дсunclassified
“…This work also highlights how conditions such as stress produce constantly fl uctuating states and describe how this is linked to the inhibitory effects of these drugs, thereby eliciting the onset of dyskinesia and ' off ' periods (Shoulson et al , 1975 ;Nutt et al , 1984 ;Durif et al , 1999 ). This is an important factor when considering the possible non-invasive methods that can help to avoid overdosing and provide anxiety reduction (Willis and Turner, 2006;Willis et al, 2012).…”
Section: Dart Exacerbates Symptom Expression: Clinical Aspectsmentioning
confidence: 99%
“…Only when the adverse effects of DART are removed from the equation does the optimal therapeutic potential become more achievable. It has been recently suggested that this may be accomplished by the application of non-invasive methods such as strategic light therapy (Artemenko and Levin , 1996 ;Paus et al , 2007 ;Willis and Turner , 2007 ) in combination with controlled DART dosing (Willis et al , 2012 ).…”
Section: Dart Exacerbates Symptom Expression: Clinical Aspectsmentioning
confidence: 99%